Role of Bone Marrow Derived Autologous stem cell Transplant in improvement of Left ventricular Ejection Fraction in dialated Cardiomyopathy. - Dr.Naveen Krishna.Kamana, Dr. Vijay Rajesh.Andanamala, .Dr. Anil Kumar Reddy.Y, Dr. Karodi. Murali Krishna (Drugs and Cell Therapies in Hematology, 2021)
Cardiomyopathy is defined as Progressive disease of myocardium orheart muscle as the heart muscle weakens and the heart loses its capability to pump blood effectively which leads to arrhythmias.Viral infections,Uncontrolled Hypertension,CAD, are the main causes of cardiomyopathy. Cardiomyopathy. There are 5 types of cardiomyopathys and we focus on the case that I have isolated autologous stemcells from the Patient where the cardiologist Dr.Karodi Murali krishna transplanted those isolated autologous stem cells through intra arterial approach into myocardium for dialated cardiomyopathy as the patient after transplant of autologous bone marrow derived stem cells left ventricular ejection fraction was improved to 45percent which was initially at the time of ailment diagnosis was 18Percent.